The Uterine Epithelium might act as a Protective Barrier for the Embryo against Exogenous Electric Fields: A Computational Study - Zahra Hajizadeh Bakhtiary; Elham Sharifi; Mehrdad Saviz; Fatemehsadat Ehsan Dehkordi (AUT Journal of Electrical Engineering)
The purpose of this article is to study the penetration of exogenous electric fields into the womb. It is postulated that the epithelial layer around the womb can act to prevent the penetration of such fields into the uterus, thereby effectively protecting the embryo from hazardous electric fields that have been shown to alter embryonic development. The very thin, low-conductivity epithelial layers are usually ignored in conventional 3D human body models used for dosimetry; i.e. to model electric field penetration in the body. However, these μm-thick layers can significantly influence the field distribution in the body due to their current blocking or barrier function. To evaluate the effect of these layers at low frequencies, the epithelial layer was manually added to the uterine tissue in a 3D human body model. Then, the field distributions across the uterus were compared with and without the epithelial layer. This preliminary study showed that considering this layer at low frequencies can cause a 60% reduction in the electric field strength within the uterus. It is anticipated that if more exact estimations of uterine epithelium resistivity become available, the model could predict yet greater reductions and higher shielding can be assumed to occur in reality.